Persistency of lactation and comparison of different persistency measures in indigenous and crossbred cows at Bako, Ethiopia - Gebreyohanes, Gebregziabher; Tegegne, Azage; Diedhiou, M.L.; Hegde, B.P. (2007)
Persistency of lactation in indigenous and crossbred cows was studied using milk data collected at Bako Agricultural Research Centre. Persistency was measured using three methods vis a vis as the ratios of milk yield during the second (P2:1) and third (P3:1) 100 days of lactation to milk yield during the first 100 days of lactation, and using persistency index (PI). The overall mean P2:1, P3:1 and PI were 78.0±0.67, 59.2±0.58 and 85.7±0.70 percent, respectively. P2:1 was significantly (P<0.01) affected by sire breed, calving season and initial milk yield, while P3:1 and PI were significantly (at least P<0.05) affected by sire breed, calving season, calving weight and initial milk yield. Among the sire breed categories, Simmental crosses had significantly the highest P2:1 (86.7±1.93%), P3:1(67.9±2.14%) and PI (90.5±1.65%) while the Horro had the lowest values of these traits. Cows that calved during Bona (December to February) had the highest P2:1 (88.2±1.58%). The lowest P3:1 (46.9±2.22 %) and PI (77.2±1.82°/a) were recorded for cows that calved during Arfasa (March to May). Calving weight was linearly related to P3:1 (b = -0.08±0.02; P < 0.001) and PI (b = 0.04±0.02; P < 0.05)_ Similarly, initial milk yield was linearly and negatively related to P2:1 (b = L14±0.31; P < 0.001), P3:1 (b = 0.88±0.38; P < 0.05) and PI (b = 0.65±0.31; P < 0.05). All persistency values obtained in this study were lower for indigenous breeds than crossbreds indicating that these traits were improved through crossbreeding. Persistency was also affected by calving season, calving weight and initial milk yield, which are probably related to the availability of feed. Thus, improving the feeding system through strategic supplementation might improve persistency in both indigenous and crossbred cows. Besides, due to shorter lactation length of most indigenous cows and for periodic assessment of persistency of crossbred cows to make improvement interventions in the meantime, P2:1 and P3:1 are more appropriate compared to persistency index.